Semiotic Analysis on Sustainable Community Farming: Multimodal Analysis, A Case Study of Community Farming at Desa Impian, Merbau Sempak, Selangor, Malaysia - Hashim, Muhamad Shahrin; Mason, Cordelia; Menon, Ami Suhana (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
The majority of global population is in the cities and most tourists are concentrated in the cities. Research on the relationship between urban farming and tourism is gaining popularity in urban studies. In Malaysia, community urban farming has been identified as a solution to sustainable development to provide food in or out of the city. This study is about how the community at Desa Impian, Merbau Sempak promotes organic vegetable farming to academicians and business communities. The idea is to promote this area as a sustainable tourism hub for researchers and business communities. This study is a multimodal semiotic analysis to better understand the dynamic of community farming culture in Malaysia. Using qualitative design and multi-layered analytical framework to explore interactive meanings construed through the functionality of various semiotic resources in multimodal narratives this study reveals the dynamic multi-layered nature of government, individual community members, and public voices about community farming culture from a Malaysian socio-cultural context. On a deeper level, farming at Desa Impian means self-identification and sharing of identity that gives rise to a sense of belonging. This study contributes to the knowledge of multimodal socio-semiotic and narrative theories on sustainable urban farming tourism in Malaysia.